Revisiting the properties of money - Isaiah Hull; Or Sattath (Sveriges Riksbank, 2021)
The properties of money commonly referenced in the economics literature were originally identified by Jevons (1876) and Menger (1892) in the late 1800s and were intended to describe physical currencies, such as commodity money, metallic coins, and paper bills. In the digital era, many non-physical currencies have either entered circulation or are under development, including demand deposits, cryptocurrencies, stablecoins, central bank digital currencies (CBDCs), in-game currencies, and quantum money. These forms of money have novel properties that have not been studied extensively within the economics literature, but may be important determinants of the monetary equilibrium that emerges in forthcoming era of heightened currency competition. This paper makes the first exhaustive attempt to identify and define the properties of all physical and digital forms of money. It reviews both the economics and computer science literatures and categorizes properties within an expanded version of the original functions-and-properties framework of money that includes societal and regulatory objectives.
Keywords: E40; E42; E50; E51; 330; Money; CBDC; Digital Currencies; Quantum Money; Currency Competition